Paleo sea-level changes and relative sea-level indicators: Precise measurements, indicative meaning and glacial isostatic adjustment perspectives from Mallorca (Western Mediterranean) - Lorscheid, T; Stocchi, P.; Casella, E.; Gómez-Pujolf, L.; Vacchi, M.; Mann, T.; Rovere, A. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2017)
Paleo relative sea-level (RSL) indicators formed during the Marine Isotope Stage (MIS) 5e have been reported bya large number of studies worldwide. Despite this, three main aspects are seldom reported: (1) use of high-precisionsurvey techniques applied to MIS 5e RSL indicators; (2) application of modern analogs to understand theindicative meaning of MIS 5e RSL indicators; (3) estimates of the effects of glacial isostatic adjustment (GIA) ontheMIS 5e records. In this study,we show howthe three points above have been addressed in a focused study onLast Interglacial outcrops on the island of Mallorca. We measured the elevation of several RSL indicators withhigh-accuracy differential GPS (vertical accuracies down to 0.1 m) and we established the relationship betweeneach RSL indicator and the paleo sea level through calculation of the indicative meaning for each RSL indicator. Inparticular,we present a novel technique to calculate the indicativemeaning of fossil beach depositswith a phaseaveragedmorphodynamicmodel (CSHORE).We showhowthis approach helps overcoming difficulties with thesurvey of themodern analogs for these indicators. Our results showthat two paleo RSLs are imprinted inMallorcaat+2.9 ± 0.8 m and +11.3 ± 1.0 m.We then compare our field-based results with modelled paleo RSL, calculatedfrom the predictions of the ice-earth coupled ANICE-SELEN model, using few different ice-sheet meltingscenarios during MIS 5e. We conclude that indicative ranges can be derived from relatively simplemorphodynamic models and that the comparison of field-derived and modelled RSL values is a good methodto validate possible scenarios of MIS 5e sea-level variability, especially in absence of precise dating.